Application of Animated Video Learning Media to Enhance Elementary Students' Ability to Understand Intrinsic Elements of Short Stories - Diah, Diah Ulfah Ningrum; Fahmi Surya, Adikira; Susiloningsih, Esti (EduStream: Jurnal Pendidikan Dasar, 2024)
This study aims to examine the improvement in students' ability to understand intrinsic elements of short stories through the application of animation-based video learning media. This study employs the Classroom Action Research (CAR) method, conducted in two cycles with a total of 78 students from three elementary schools. Each cycle involves the stages of planning, action, observation, and reflection. The study results indicate a significant increase in student engagement and comprehension. In the first cycle, 57% of students achieved the Minimum Completeness Criteria (MCC), while in the second cycle, this percentage rose to 89%. The use of animated media has proven effective in enhancing students' learning motivation and their understanding of intrinsic elements of short stories, such as theme, character, and setting. It is suggested that animation-based learning media be used more frequently in literature lessons in elementary schools to boost active participation and student learning outcomes. Additionally, it is recommended that teacher training in designing and implementing animation-based media be improved to ensure optimal application in various schools. Further research is also recommended to test the effectiveness of animated media on other learning materials and to explore its impact on students' critical thinking skills and creativity in various learning contexts.